2018
DOI: 10.1177/0954405417752528
|View full text |Cite
|
Sign up to set email alerts
|

Effect of slotted electrodes on improvement in machining performance of large-scale electrical discharge machining

Abstract: Under special conditions, electrical discharge machining is prone to experiencing poor machining removal rate. This creates debris deposits that lead to decreased machining efficiency and poorer machining quality in the machining workpieces during machining operations. Thus, the present study investigated the use of slotted electrodes to improve machining debris removal and compared the machining capability of such electrodes with that of cylindrical, nonslotted electrodes. Concurrently, oscilloscopes were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…However, the forming accuracy of porous electrodes is poor, leaving a large margin for subsequent processing, and the process is more complicated. Jie-Shing Lo et al [12] investigated the use of slotted electrodes to improve machining debris removal and compared the machining capability of such electrodes with that of nonslotted electrodes. Compared with general nonslotted electrodes, the deep slotted electrodes improved the material removal rate on large-scale and hemisphere electrical discharge machining result by 91% and 116.7%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, the forming accuracy of porous electrodes is poor, leaving a large margin for subsequent processing, and the process is more complicated. Jie-Shing Lo et al [12] investigated the use of slotted electrodes to improve machining debris removal and compared the machining capability of such electrodes with that of nonslotted electrodes. Compared with general nonslotted electrodes, the deep slotted electrodes improved the material removal rate on large-scale and hemisphere electrical discharge machining result by 91% and 116.7%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the fourslotted electrode can provide optimal EDM efficiency and that using slotted electrodes significantly reduces the electrode wear rate. Jie-Shing Lo et al [24] investigated the use of slotted electrodes to improve the removal of erosion products. They analyzed the waveforms of machining voltage and current signals to gain the electrical discharge condition of EDM.…”
Section: Introductionmentioning
confidence: 99%
“…In this aspect, a simple cylindrical tool is modified to improve flushing and machining performance. Various types of tool geometry used by researcher are foil, 10 slotted, 11,12 stepped, 13 peripheral slots, 14 bunched, 15 tubular, 16 semi-cylindrical, 17 inclined micro-slots, 18 helical slots, 19 single and double-helical, 20 and 3D printed complex profile 21 to improve machining performance. However, all the study was focused on the experimentation to enhance material removal rate and reduce tool wear rate.…”
Section: Introductionmentioning
confidence: 99%